Peningkatan Pemahaman Siswa Tentang Akhlak Terpuji Melalui Media Audio-Visual pada Mata Pelajaran FAI di Kelas III SDN 068 Rumbio - Nur Adilah; Rukiah Hsb; Siti Aminah; Juli Artisah Nasution; Masdinar Pulungan (PANTAK: Jurnal Penelitian Tindakan Kelas, 2025)
This community service aimed to improve students' understanding of praiseworthy morals through audio-visual media in Islamic Religious Education (FAI) subject at grade III of SDN 068 Rumbio. The implementation involved 25 students and utilized interactive audio-visual media including animated videos, moral stories with visual illustrations, and educational games. Pre-test and post-test methods were employed to measure students' understanding improvement, along with observation and interviews. Results showed significant improvement in students' understanding of praiseworthy morals, with average scores increasing from 65.2 to 83.4. Students demonstrated better comprehension of moral concepts such as honesty, respect, cooperation, and responsibility. The audio-visual media proved effective in engaging students and making abstract moral concepts more concrete and understandable. Teachers also reported positive responses regarding the implementation of this innovative learning approach. The success factors included appropriate media selection, active student participation, and strong support from school management.